1992
DOI: 10.1136/adc.67.10_spec_no.1169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of patency of the ductus arteriosus on blood pressure in very preterm infants.

Abstract: Forty one preterm infants (birth weight <1500 g) were studied by daily Doppler echocardiography for the first week of life to examine the effect of a haemodynamically significant ductus arteriosus (HSDA) on systemic blood pressure. Hourly records of blood pressure were averaged for each infant to produce a 24 hour mean value and the infants were then allocated to groups according to whether, by echocardiographic criteria, there was a HSDA on that day.In infants from 1000 to 1500 g the differences in all parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(66 citation statements)
references
References 8 publications
1
62
1
2
Order By: Relevance
“…We focused on the first 24 hours of life because that is when there is a need for diagnosis and treatment for hypotension 12,14 and because, later, many variables such as a patent ductus arteriosus precluded the recognition of a stable population. 28 In defining our stable group, like others, we excluded factors that affect blood pressure 8 -10 but allowed others, such as history of preeclampsia and antenatal steroids, that are now known not to influence MAP in ELBW infants. 11,14 Reference values extrapolated from linear regression models of larger and more mature infants have been found to be inaccurate 23,24 and have not addressed special populations such as ELBW infants and concordant and discordant twins.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the first 24 hours of life because that is when there is a need for diagnosis and treatment for hypotension 12,14 and because, later, many variables such as a patent ductus arteriosus precluded the recognition of a stable population. 28 In defining our stable group, like others, we excluded factors that affect blood pressure 8 -10 but allowed others, such as history of preeclampsia and antenatal steroids, that are now known not to influence MAP in ELBW infants. 11,14 Reference values extrapolated from linear regression models of larger and more mature infants have been found to be inaccurate 23,24 and have not addressed special populations such as ELBW infants and concordant and discordant twins.…”
Section: Discussionmentioning
confidence: 99%
“…After this time, pulmonary pressure continues to fall and ductal shunting has increased impact on blood pressure (4,33) and patterns of cerebral perfusion (34,35). In addition, it should be noted that the finding that upper body perfusion is maintained in the presence of ductal shunt is drawn from mean values seen across a large cohort of preterm infants, and it is clear that the transitional circulation varies greatly between individuals (17,36).…”
mentioning
confidence: 99%
“…Several studies focusing on blood pressure and PP during PDA in preterm infants during the first days of life have been reported. Evans and Moorcraft (14) found that both SAP, DAP and MAP were not lower in infants weighing 1000-1500 g with PDA compared with infants without PDA. Differences in SAP, DAP, and MAP were found in infants weighing less than 1000 g with PDA compared with infants without PDA (14,15).…”
Section: Gevers Et Almentioning
confidence: 99%